The Concept of Developing Islamic Educational Institutions - Irwandi Siregar, Hendra; Hannum Hasibuan, Kholidah; Purnama, Rizkiyah; Sihombing, Irwandi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Islamic education plays a strategic role in shaping a generation that is faithful, knowledgeable, and of noble character. Islamic values serve as an essential foundation in building a harmonious and just society, while also contributing to global civilization. However, Islamic educational institutions, such as pesantren (Islamic boarding schools), madrasas, and Islamic universities, face global challenges including technological advancements, globalization, and socio-cultural changes. Therefore, continuous innovation and development are needed to maintain the relevance and competitiveness of Islamic education. This paper uses a literature study method to analyze the concept of developing Islamic educational institutions, the challenges faced, and effective strategies for their development. The discussion results show that the development of Islamic educational institutions requires a holistic approach, including improving the quality of human resources, curriculum innovation that integrates religious knowledge and modern science, the use of technology, and collaboration with various parties. With these steps, Islamic education is expected to produce individuals who are spiritually, intellectually, and morally superior, and to become institutions that are relevant and contribute to building a civilization based on Islamic values.